KPMG banking survey Nigeria 1998 (Nigeria Jaylaw, 1998)
This is the third edition of the KPMG Nigeria Annual Banking Survey. It provides information ad statistics on most of the banks licensed and operating in Nigeria
aia 5/9/16 p
Ref.
Keywords: Banking - surveys; KPMG; Nigeria